2010
DOI: 10.1038/jhg.2010.53
|View full text |Cite
|
Sign up to set email alerts
|

Common polymorphisms in ITGA2, PON1 and THBS2 are associated with coronary atherosclerosis in a candidate gene association study of the Chinese Han population

Abstract: Coronary atherosclerosis is a complex and progressive condition that involves many biological pathways, including the oxidative stress and inflammatory response pathways. To investigate the association between common genetic variation within these two pathways and coronary atherosclerosis, we performed a comprehensive two-stage candidate gene association study in a Chinese Han population. In stage I, 936 tag single-nucleotide polymorphisms (SNPs) within 116 candidate genes were genotyped in 293 coronary athero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…Previous studies offer insights into the observed associations. For example, common polymorphisms in ITGA2 (an ITGA7 homolog) were associated with coronary atherosclerosis in a candidate gene association study of the Chinese Han population (36). Variants in CEP164 and CEP68, which are homologs of CEP72, were reported to be associated with TG and LDL-C fasting levels (5, 21, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies offer insights into the observed associations. For example, common polymorphisms in ITGA2 (an ITGA7 homolog) were associated with coronary atherosclerosis in a candidate gene association study of the Chinese Han population (36). Variants in CEP164 and CEP68, which are homologs of CEP72, were reported to be associated with TG and LDL-C fasting levels (5, 21, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the potential role of PON1 in lipid transfer from LDL-C to HDL-C, it is likely that decreased serum PON1 activity is associated with the increased LDL-C in the olanzapine group. Interestingly, serum PON-1 activity is reported to be negatively correlated with serum LDL-C level 51,52. Furthermore, our finding of a positive correlation between serum PON1 activity and HDL-C level in the olanzapine group is of great interest.…”
Section: Discussionmentioning
confidence: 58%
“…Three studies (two European [10,33] and one Japanese [34]) were conducted without “proper” controls of no CHD history and were also excluded. One additional Chinese study met the inclusion criteria but was excluded due to unavailability of essential information even after contacting the authors [35]. The 9 remaining studies, together with PROCARDIS [25] and CARDIoGRAM [24] studies, were included in the meta-analysis (Table 1) [11,14,16,20-23,36,37].…”
Section: Resultsmentioning
confidence: 99%